2019
DOI: 10.3390/cells8050459
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of miR-29 Leads to Myopathy that Resemble Pathology of Ullrich Congenital Muscular Dystrophy

Abstract: Ullrich congenital muscular dystrophy (UCMD) bring heavy burden to patients’ families and society. Because the incidence of this disease is very low, studies in patients are extremely limited. Animal models of this disease are indispensable. UCMD belongs to extracellular matrix-related diseases. However, the disease models constructed by knocking out some pathogenic genes of human, such as the Col6a1, Col6a2, or Col6a3 gene, of mice could not mimic UCMD. The purpose of this study is to construct a mouse model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 68 publications
(84 reference statements)
1
12
0
Order By: Relevance
“…Previous studies have also suggested that YAP1 can facilitate the proliferation of SMSCs (Watt et al, 2010;Liu et al, 2017) but inhibit their differentiation (Sun et al, 2017). Previous studies have also suggested that miR-29a can inhibit the growth of skeletal muscle (Wang et al, 2011;Liu C. et al, 2019) and the proliferation of satellite cells and promote the differentiation of satellite cells (Kapinas et al, 2010;Wei et al, 2013). Our results also showed that miR-29a can inhibit the proliferation of SMSCs, which is consistent with previous studies.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Previous studies have also suggested that YAP1 can facilitate the proliferation of SMSCs (Watt et al, 2010;Liu et al, 2017) but inhibit their differentiation (Sun et al, 2017). Previous studies have also suggested that miR-29a can inhibit the growth of skeletal muscle (Wang et al, 2011;Liu C. et al, 2019) and the proliferation of satellite cells and promote the differentiation of satellite cells (Kapinas et al, 2010;Wei et al, 2013). Our results also showed that miR-29a can inhibit the proliferation of SMSCs, which is consistent with previous studies.…”
Section: Discussionsupporting
confidence: 92%
“…For example, the disruption of miR-29 leads to abnormal differentiation of vascular smooth muscle cells (Cushing et al, 2015) and contributes to dystrophic muscle pathogenesis (Wang et al, 2012). However, the overexpression of miR-29 can also lead to congenital muscular dystrophy (Liu C. et al, 2019). These findings suggest that miR-29 may play different roles in different species and tissues.…”
Section: Introductionmentioning
confidence: 99%
“…All mice, which were raised in specific pathogen-free environments and temperature (25°C -1°C), humidity (60-70%), and lighting (a 12 h light and 12 h dark cycle), were regulated. The miR-29ab1 and miR-29b2c double knockout mice (dko) (Ge et al, 2019) and the miR-29ab1 cluster overexpression (dTG) mice were previously reported (Liu et al, 2019). miR-29a/b1 null and miR-29b2/c null mice (Ge et al, 2019) were purchased from Cyagen Biosciences (Beijing, China).…”
Section: Micementioning
confidence: 99%
“…To generate the TRE-miR-29a/b1 construct, the mmu-miR-29a/b1 coding sequence was amplified (forward primer: 5 0 -GGACTT CACCTTCCCTCTCC-3 0 and reverse primer: 5 0 -ATTGGTTTGGCCCTTTATCC-3 0 ), cloned into the pTRE2 vector (Clontech, Palo Alto, CA, USA) and sequenced (Liu et al, 2019). The Axin2-LacZ (stock no: 009120), teto-Cre (stock no: 006234), K14-rtTA (stock no: 007678) and K14-Cre (stock no: 004782) transgenic mouse lines were obtained from the Jackson Laboratory.…”
Section: Micementioning
confidence: 99%